Influence of High Temperature and Ammonia and Nitrite Accumulation on the Physiological, Structural, and Genetic Aspects of the Biology of Largemouth Bass (Micropterus salmoides) - Yuexing Zhang; Hui Qiao; Leyang Peng; Yujie Meng; Guili Song; Cheng Luo; Yong Long (Antioxidants)
Hyperthermia and nitrogenous pollutants like ammonia and nitrite are common risk factors that adversely affect fish health and pose significant threats to the aquaculture industry. However, the impacts of high temperatures on the accumulation of nitrogenous pollutants in the water of the aquaculture systems and their toxicity to farmed fish are not well understood. In this study, juvenile largemouth bass (Micropterus salmoides, LMB) were kept at 28 °C and 34 °C in a closed aquatic system to investigate the effects of higher temperatures on ammonia and nitrite accumulation. The fish were fed 2% of their body weight daily for a 14-day experiment. Ammonia levels gradually increased, peaking on day 7 at 34 °C and on day 9 at 28 °C, then decreased to near zero. Nitrite levels remained low initially and increased rapidly along with the reduction in ammonia levels at both temperatures. The 34 °C high temperature accelerated the accumulation of ammonia and its transformation into nitrite compared to 28 °C. Fish were sampled on day 1 (low ammonia and low nitrite, LALN), day 8 (high ammonia and low nitrite, HALN), and day 14 (low ammonia and high nitrite, LAHN) to explore toxic effects. Successive exposure to high levels of ammonia and nitrite caused oxidative stress in the liver and significant pathogenic changes in the liver and spleen, with more pronounced impacts observed at 34 °C. Significant changes in gene expression were detected in the liver and spleen of fish sampled at HALN and LAHN, compared to those at LALN, with upregulated genes primarily associated with extracellular matrix (ECM) and cytoskeleton organization. A second experiment was conducted at the same temperatures but without ammonia/nitrite accumulation. The results of this experiment confirmed the combined effects of hyperthermia and ammonia/nitrite toxicity on the expression of genes involved in ECM–receptor interaction and TGF-beta signaling. These findings are valuable for optimizing cultivation environments and promoting the health of farmed LMB.